Ventilated cavitating flow over a bluff body with special emphasis on the vortex-cavitation interaction. (1st December 2020) - Yanan, Zheng; Zhiying, Wang; Guoyu, Wang
Abstract: The objective of this paper is to investigate the vortex-cavitation interaction in ventilated cavitating flow over a bluff body at Reynolds number Re  = 6.7 × 10 4 by numerical method. The results present that in the active cavitation area, the turbulent kinetic energy mainly distributes in the leading edge of the cavity and the gas-liquid interface of the shedding vortex. The intensity variation is closely related to the cavity morphology and the ventilated cavitation development. With the increase of the gas entrainment coefficient Q v, the ventilated cavitation reduces the turbulence intensity. Three well-employed vortex identification methods, ω z criterion, Q criterion and the improved Ω method, are applied to identify the vortex structures. The comparison shows that the improved Ω method can well capture the vortices of different intensity in the cavitating flow field without using the threshold value, especially for the formation of the vortices. As for the ventilated cavitation vortex dynamics, strong rotation appears with the shear layer rolling up and relatively strong shear occurs with the entrainment of vortices during the vortex formation. With the increase of Q v, both the rotation and shear in the active cavitation area tend to become weaken owing to the reduction of turbulent intensity. Highlights: The vortex-cavitation interaction in ventilated cavitating flow is investigated by numerical method. The unsteady behaviors with ventilated cavitation development are discussed. The ω z criterion, Q criterion and the improved Ω method, are applied to identify the cavitation vortex structures. Rotation and shear in the ventilated cavitation vortex dynamics are analyzed.